Building Students’ Self-Confidence in Speaking English for Presentation in Online Classes - Arni (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
This study discusses building student’s self-confidence in Speaking English for Presentation in an online class. The aim of this study is to investigate the practice of stressing (word stressing and sentence stressing), speech chunk (chunking and pausing), and intonation in students’ speaking skill with purpose for building students’ self-confidence to speak English effectively in online classes. The data taken in this study were gained from students’ responses towards the use of stressing, chunking and intonation contributing in building their self-confidence in their English language speaking skill. The students involved in this study were those taking online English 3 class as a compulsory subject course in a private higher institution in Bandung West Java Indonesia. The results indicate that the most of students perceive positively that the use of stressing, chunking and intonation in English speaking skill for presentation are helpful to encourage them to participate in Speaking English for Presentation in an online class and contribute in building their self-confidence to speak English.